Auditory central pathways in children and adolescents with multiple sclerosis - Dayane Aparecida Nascimento Barbosa; Liliane Aparecida Fagundes Silva; Alessandra Giannella Samelli; José Albino da Paz; Carla Gentile Matas (Arquivos de Neuro-Psiquiatria)
Background Multiple sclerosis (MS) is an inflammatory demyelinating disease. Auditory evoked potential studies have demonstrated conduction and neural processing deficits in adults with MS, but little is known about the electrophysiological responses in children and adolescents.